WU Polyomavirus Infection in Children With Acute Lower Respiratory Tract Infections in China, 2017 to 2019: Case Reports and Multicentre Epidemiological Survey - Zhao, Hongwei; Xu, Wenmiao; Wang, Lijuan; Zhu, Yun; Wang, Xiaohui; Liu, Yingchao; Ai, Junhong; Feng, Qianyu; Deng, Li; Sun, Yun; Li, Changchong; Jin, Rong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
WU polyomavirus (WUPyV) is a novel member of the family Polyomaviridae recently detected in respiratory tract specimens. So far, it has not been proven whether WUPyV is a real causative agent for respiratory diseases. In this study, we described two patients with fatal infection who had WUPyV detected in their nasopharyngeal swabs. Furthermore, we conducted a multicentre study in six hospitals from different districts of China. WUPyV was detected by real-time polymerase chain reaction assays, and the clinical and molecular epidemiological characteristics of WUPyV strains among hospitalized children with acute lower respiratory tract infections all around China from 2017 to 2019 were analysed. Two complete WUPyV genome sequences were assembled from fatal patients’ airway specimens. Phylogenetic tree analysis revealed that they were most closely related to strains derived from Fujian and Chongqing, China, in 2008 and 2013, respectively. In 2017–2019, a total of 1,812 samples from children with acute lower respiratory tract infections were detected for WUPyV, of which 11 (0.6%) were positive. Children aged ≤5 were more susceptible to WUPyV infection. A total of 81.8% of WUPyV-positive patients were coinfected with other viruses, of which rhinovirus enjoyed the highest frequency. The main clinical symptoms of infected patients include fever, coughing and sputum expectoration. Most patients were diagnosed with pneumonia, followed by bronchial surgery. Three patients manifested severe infection, and all patients improved and were discharged. Our results show that WUPyV persistently circulates in China. Further investigations on the clinical role and pathogenicity of WUPyV are necessary.